2007
DOI: 10.1007/s11418-007-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

HPLC profile and antihyperglycemic effect of ethanol extracts of Andrographis paniculata in normal and streptozotocin-induced diabetic rats

Abstract: Andrographis paniculata is a Malaysian traditional herb for treatment of fever-causing diseases and diabetes. The aim of the present study was to examine the antihyperglycemic effects of different extracts (95, 50, and 20% ethanol extracts and water extracts) of A. paniculata in normal and streptozotocin-induced diabetic rats. Only the treatment with 20% ethanol extract (at 1 g/kg for 7 h, p.o.) significantly (P < 0.01) reduced the rise in blood glucose levels in glucose-loaded rats. None of the different extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…At the end of the experimental period, blood samples were collected for the measurement of blood glucose level and plasma insulin. An intraperitoneal glucose tolerance test (IPGTT) was performed at the end of 14-day treatment [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experimental period, blood samples were collected for the measurement of blood glucose level and plasma insulin. An intraperitoneal glucose tolerance test (IPGTT) was performed at the end of 14-day treatment [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected from the tail vein at time –60 min (just before the administration of the extract by gastric intubation), time 0 (prior to the glucose load) and 15, 30, 45, 60, 90 and 120 min after the glucose load. Blood glucose concentration was measured using the Accu-check Advantage II Clinical Glucose meter (Roche diagnostics Co. USA) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, a study by Ahmad et al (2007) determined the antihyperglycemic effects of different extraction solvents in normal and streptozotocin-induced diabetic rats. Aerial parts of A. paniculata were extracted with different concentration of ethanol (20%, 50%, and 95%) and distilled water by using reflux techniques at 40 °C for 3 days.…”
Section: Overview Of Studies Regarding Extraction Techniques and The mentioning
confidence: 99%
“…monograph. Several HPLC methods have been reported for the qualitative and quantitative determination of andrographolides [8][9][10]. A detailed evaluation of the literature data showed that the reported HPLC methods suffer from extremely fast run times that may not afford a detailed chromatographic fingerprint or do not include an exhaustive extraction of the raw material.…”
Section: Edqmmentioning
confidence: 99%